SimuVet: a preliminary study of the innovative development of a simulator for epidural anesthesia training in dogs - Lobo Moraes, Paloma; Ghisi, Lianna; Paes de Barros, Anna Júlia B.; de Carvalho Peixoto, Vithor Hugo; Brandini Népoli, Pedro Eduardo; Moleta Colodel, Edson; Souza de Lima, Luiz Felipe; Lopes de Souza, Roberto (Frontiers in Veterinary Science, 2024)
Epidural anesthesia in dogs is a locoregional anesthesia technique used in veterinary medicine, becoming an important integrated application in the anesthetic protocol to provide safer and more effective analgesia to patients. For this, professionals must adhere to rigorous guidelines and possess technical skills. In this context, in veterinary education, the development of practical clinical skills represents a crucial aspect in the training of these professionals. However, traditional teaching methods have proven insufficient to ensure a consistent level of competence among recent graduates.The introduction of non-animal alternatives for educational purposes has contributed to the development of simulation-based teaching, an innovative and accessible field capable of enhancing pre-clinical proficiency in students and reducing the use of live animals and cadavers. Despite its application in various areas of veterinary education, there are no conclusive results regarding the development of accessible simulators capable of effectively enhancing training in epidural anesthesia in dogs. Therefore, this article represents a pioneering study aimed at sharing a method for creating SimuVet, a realistic simulator for training epidural anesthesia in dogs. The simulator was fully developed by veterinary researchers with limited experience in 3D printing and, after preliminary analysis, demonstrated excellent performance and ultrasonographic anatomy. Future work will focus on the formal validation of this simulator with the aim of improving the teaching and learning process for students and experts in performing epidural anesthesia in companion animals.